2021
DOI: 10.1002/cti2.1256
|View full text |Cite
|
Sign up to set email alerts
|

Complement factor D haplodeficiency is associated with a reduced complement activation speed and diminished bacterial killing

Abstract: Objectives Complete deficiency of alternative pathway (AP) complement factors, explained by homozygous mutations, is a well‐known risk factor for invasive bacterial infections; however, this is less obvious for heterozygous mutations. We describe two siblings with a heterozygous NM_001928.3(CFD):c.125C>A p.(Ser42*) mutation in the complement factor D (fD) gene having a history of recurrent bacterial infections. We determined the effect of heterozygous fD deficiency on AP complement activity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“… 55 This shows that bacterial infections are an important safety concern for patients taking complement inhibitors. To date, only two individuals with factor B deficiency 124 , 125 and 13 individuals with factor D deficiency have been identified, 70 , 126 , 127 , 128 , 129 , 130 , 131 who were discovered based on a history of infections with encapsulated bacteria, (for example, Neisseria meningitidis, Haemophilus influenzae, Staphylococcus aureus, Streptococcus pyogenes ) in at least one family member. While 10 of the 13 individuals with factor D deficiency had a history of infections, this was not the case for the other three.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 55 This shows that bacterial infections are an important safety concern for patients taking complement inhibitors. To date, only two individuals with factor B deficiency 124 , 125 and 13 individuals with factor D deficiency have been identified, 70 , 126 , 127 , 128 , 129 , 130 , 131 who were discovered based on a history of infections with encapsulated bacteria, (for example, Neisseria meningitidis, Haemophilus influenzae, Staphylococcus aureus, Streptococcus pyogenes ) in at least one family member. While 10 of the 13 individuals with factor D deficiency had a history of infections, this was not the case for the other three.…”
Section: Discussionmentioning
confidence: 99%
“… 69 Initially, factor D was thought to be the rate‐limiting protease of the alternative pathway, based on low plasma concentrations and studies with reconstituted factor D deficient plasma. 70 , 71 However, more recently it has become clear that in diseases with increased alternative pathway activity, such as C3G, very low levels of factor D (~1% of plasma levels) are sufficient to activate the alternative pathway, especially if the C3 convertase is stabilized. This also suggested that >90% of enzyme inhibition may be required to fully shut down the alternative complement pathway.…”
Section: Complement Factor D As a Drug Targetmentioning
confidence: 99%